2019
DOI: 10.26479/2019.0503.25
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The seedling morphology of eleven taxa of Amaranthaceae has been investigated. Among the 31 seedling morphological characters, the characters like length, surface of hypocotyl; apex, shape, surface, petiole of paracotyledons; base, apex, surface, margin, petiole of first two leaves; phyllotaxy, apex, surface, base of subsequent leaves (eophylls); length, surface of epicotyl appeared to be useful. Following the methods of numerical taxonomy, i.e. Cluster Analysis, Principal Component Analysis, the seedling morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In this case PCA has important role in identifying morphological variation patterns [23] and in determining the relative contribution of characters to the variations found in samples under study [3]. Due to its complementary role, PCA was commonly used in conjunction with cluster analysis in taxonomic studies at family, genus, and species level such as those reported on Amaranthaceae [33], Abelmoschus [34], and Mangifera indica [35]. Accordingly, combination of these two multivariate analysis methods, the cluster analysis and PCA, has also been applied widely in sorghum diversity studies [12,27,28,36,37].…”
Section: Resultsmentioning
confidence: 99%
“…In this case PCA has important role in identifying morphological variation patterns [23] and in determining the relative contribution of characters to the variations found in samples under study [3]. Due to its complementary role, PCA was commonly used in conjunction with cluster analysis in taxonomic studies at family, genus, and species level such as those reported on Amaranthaceae [33], Abelmoschus [34], and Mangifera indica [35]. Accordingly, combination of these two multivariate analysis methods, the cluster analysis and PCA, has also been applied widely in sorghum diversity studies [12,27,28,36,37].…”
Section: Resultsmentioning
confidence: 99%